2022
DOI: 10.1002/admi.202102346
|View full text |Cite
|
Sign up to set email alerts
|

Pickering Emulsions Stabilized by Halloysite Nanotubes: From General Aspects to Technological Applications

Abstract: Besides surfactants, which decrease the interfacial tension between two immiscible liquids, also interfacially active particles can successfully stabilize an emulsion system by attaching at the liquid–liquid interface. The preparation of the resulting Pickering emulsions has been so far investigated starting from the study of the interactions arising between the dispersed droplets and the stabilizers, till the application of these systems in a wide range of different fields. This work is intended to provide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 206 publications
(356 reference statements)
0
23
0
Order By: Relevance
“…Previous studies , suggested that the wettability of nanomaterials determined the type of water–oil emulsion (W/O or O/W). In addition, the surface charge of the adsorbed particles is also an essential parameter to control the stability of Pickering emulsion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies , suggested that the wettability of nanomaterials determined the type of water–oil emulsion (W/O or O/W). In addition, the surface charge of the adsorbed particles is also an essential parameter to control the stability of Pickering emulsion.…”
Section: Resultsmentioning
confidence: 99%
“…During the preparation and application of Pickering emulsions, wettability, size, surface properties, and concentration of emulsifier particles play a critical role . It has been demonstrated that HNTs can be successfully used in the preparation of Pickering emulsions. , There have been considerable studies on loading chemicals into the lumen of HNTs or grafting them on the outer surface to prepare functional Pickering emulsions for different applications . However, HNTs have good water dispersion ability, which is contrary to the moderate wettability required by emulsifier particles.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Among all clay-based species, halloysite nanotubes (HNTs), one of the most well-known clay materials, are particularly preferred for drug delivery due to their unique morphology. [16][17][18] According to the literature, the rod-shaped morphology (also needles and tubes) of drug carriers signicantly affects the cell adhesion, internalization, and uptake processes. 19,20 As a result, more of the administered nanocargo is taken by the living cells during a short contact time, resulting in more efficacy.…”
Section: Overviewmentioning
confidence: 99%
“…The difference in charge is a direct consequence of the chemical composition [ 21 , 22 ]. Halloysite is composed of a layer of a Si-centred tetrahedra overlapped to a layer of an Al-centred octahedra in a kaolinite-like structure [ 23 ]. Then, this kaolinite sheet rolls up to confer the nanoclay and its peculiar morphology and charge separation, bearing Si-O-Si groups outside and Al-OH groups in the inner lumen [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Halloysite is composed of a layer of a Si-centred tetrahedra overlapped to a layer of an Al-centred octahedra in a kaolinite-like structure [ 23 ]. Then, this kaolinite sheet rolls up to confer the nanoclay and its peculiar morphology and charge separation, bearing Si-O-Si groups outside and Al-OH groups in the inner lumen [ 23 ]. The dimensions of the nanotubes depend on the natural deposit, but generally, the length is in the 0.5–2 µm range, the external diameter is 50–200 nm and the internal diameter is 15–50 nm, respectively [ 24 ].…”
Section: Introductionmentioning
confidence: 99%